1971
DOI: 10.1542/peds.48.4.595
|View full text |Cite
|
Sign up to set email alerts
|

Hyperammonemia Due to a Mutant Enzyme of Ornithine Transcarbamylase

Abstract: In a case of congenital hyperammonemia described in an 8½-month-old girl, elevated blood ammonia was shown to result from a mutant enzyme of ornithine transcarbamylase. An in vitro study indicated a decrease in affinity of the enzyme for carbamyl phosphate but not for ornithine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
1997
1997

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The normal hepatic OCT observed in our study was supported by the serum urea levels and the amino acid pattern. Elevation of serum urea and reduction of glutamine and lysine, and a normal level of glutamate in severe and less severe Zn-deficient animals, are in conflict with the observation for congenital OCT deficient patients for whom characteristic findings in the serum were normal or sometimes included lower levels of urea and elevated levelsof glutamate, glutamine, and lysine (13,14). Our Experimental groups mU/g wet weight mU/mg protein observation is comparable to that of Hsu et al (5) who found increased urea excretion in Zn-deficient rats and reported that this was attributable to protein catabolism associated with elevated arginase activity.…”
Section: Enzyme Studymentioning
confidence: 98%
“…The normal hepatic OCT observed in our study was supported by the serum urea levels and the amino acid pattern. Elevation of serum urea and reduction of glutamine and lysine, and a normal level of glutamate in severe and less severe Zn-deficient animals, are in conflict with the observation for congenital OCT deficient patients for whom characteristic findings in the serum were normal or sometimes included lower levels of urea and elevated levelsof glutamate, glutamine, and lysine (13,14). Our Experimental groups mU/g wet weight mU/mg protein observation is comparable to that of Hsu et al (5) who found increased urea excretion in Zn-deficient rats and reported that this was attributable to protein catabolism associated with elevated arginase activity.…”
Section: Enzyme Studymentioning
confidence: 98%